A New Resonance Based Single-Switch Pfc Converter - Bodur, Haci; Akboy, Erdem (ISTANBUL UNIV-CERRAHPASA, 2021)
In this study, a novel resonance-based single-switch and single-stage power factor correction (PK) converter is proposed. 1 his converter achieves soft switching (SS), thereby minimizing switching losses. The converter draws current from the line in a sinusoidal form during each switching pedal, which provides high PR: with decreased electromagnetic interference. Furthermore, the proposed converter transfers most of the input energy directly to the output, providing direct power transfer with high efficiency using a forward-flyback converter. The rest of the input energy is transferred to the output via a flyback converter to obtain high output regulation. At this converter, PFC circuit, forward and flyback converters share only one switch. The theoretical analysis of this resonance-based single-switch and single-stage PFC converter is verified by a prototype output of 200 W/120 V with a 100-kHz switching frequency.
Keywords: Soft switching; power factor correction; resonance converter; SNUBBER CELL; Engineering